(untitled) (American Journal of Islam and Society, 2003)
This book represents the "female" side of a new genre in Islamic publishing. Jones, a white American convert, educated, well-read, and passionate about her native tongue and its literature, writes of her experiences as a female convert to Islam and, as the saying goes, ’’tells it like it is." Like Jeffrey Lang, who provides the foreword, the author puts into words the confusion, hurt, bewilderment, and anguish that many converts feel after they come down from the giddy heights of"saying their shahadah," - experiences that may all but extinguish the initial spark of excitement and enthusiasm. The book traces Jones’ progress from initial conversion and community involvement, to "burn-out’’ and withdrawal, and on to her recovery from depression and marital difficulties. In a pattern familiar to many converts, the initial spiritual delight - even euphoria - is soon swamped by layer upon layer of community-induced confusion, rebuffs, snubs, dogmatism, and even racism. She speaks with reference to her interaction with the Arab community, but the pattern will be familiar to many of those who are either converts to Islam and/or partners in mixed marriages. Jones introduces the Muslim community to the idea of "personal authenticity" and suggests that converts may suffer greatly when they lose their own ethnic or cultural identity in the effort to become more like the born-Muslim community in which they find themselves. While this is an interesting idea, a brief search of such terms via my favorite web search engine led to a host of gay and lesbian sites. Not knowing the pre cise origin of the notion of "personal authenticity," it wou Id appear to be a matter that should be handled with caution. The author frankly discusses depression, instead of accepting its being swept under the carpet and dismissed as "madness" or the product of weak faith ... and, therefore, one’s own fault. This is another area that deserves the Muslim community’s further attention, and in which Jones blazes a longoverdue trail. In addition to the spiritual approach, she provides some practical tools for dealing with it, such as journaling and physical exercise. This brings us back to the issue pertaining to the loss of identity and personal authenticity, as she asks: How can you come to prayer without your heart? Jones also touches upon women’s issues. The chapter on "The American Harlot," which makes for painful reading, highlights the ...